Therapeutic virtual reality in prison: Participatory design with incarcerated women. (August 2021) - Teng, Melissa Q; Gordon, Eric
Upon release from prison, women face barriers in every step of their journey home, with most reentry services designed for men. With virtual reality (VR) headsets increasingly affordable and normalized as a mental health treatment modality, VR is being adopted by prisons around the United States. We argue that the risks and affordances of VR in this political context necessitate centering those with lived experience as creative agents to avoid designing media that re-traumatizes, reduces the complexities of reentry, and reproduces oppressive prisoner–guard dynamics. This article documents and analyzes the design process of a VR reentry program for a state prison to help incarcerated women practice responding to high-stress reentry situations, prior to their release. The resulting VR prototype draws on therapeutic VR work but takes a community-based participatory design approach. We conclude by discussing the institutional and cultural tensions of implementing a participatory design process in a US state prison system.